ANALISA PENGARUH TEMPERATUR TUANG DAN TEMPERATUR CETAKAN TERHADAP KEMUNGKINAN MUNCULNYA CACAT RETAK MAKRO PADA PENGECORAN SQUEEZE BENDA TIPIS ALUMINIUM DAUR ULANG - Elfendri - (Jurnal APTEK, 2010)
Squeeze casting Al-Si casting is the process whereby the liquid Al-Si metal recycling frozen under high pressure so that it will reduce the amount of porosity defects,but tends to experience hot cracking.Parameter of the silicon content of recycled aluminum, cast and mold temperature affects the occurrence of hot cracks in the thin cast body.This study aims to analyze the influence of silicon content, casting and mold temperature on the occurrence of hot cracking in squeeze casting process of thin aluminum recycled objects so that preventive action can be done on the production process.This squeeze casting using hydraulic pressure 135 MPa.Temperatures used are220, 275 and 3300C for mold and 665, 775 and 8850C for the liquid metal. Silicon content of recycled aluminum used are: 0.45, 3.22 and 6.04% weight.Long and hot cracking index is used as measurable indicators of heat cracks.Increasing silicon content will lower the crack length and the index of thin cast aluminum body heat recycling. Increasing temperature and mold castings will increase the length and thermal cracking index aluminum thin cast object of recycling. The combination of casting and mold temperatures low and high silicon composition will produce athin cast aluminum body free of crackedheatrecycle.